Educational Financing in Canada 1970-71 to 1984-85: Who Calls the Tune, Who Pays the Piper? - Decore, Anne Marie; Pannu, Raj S. (Canadian Journal of Higher Education, 1986)
This study examines changes in educational financing since 1970- 71, looking at provincial differences in funding in relation to GDP, total government expendi- tures, enrolments and funding for elementary-secondary and tertiary schooling, as well as in relation to the funds contributed by each level of government. Since the late 1970's reductions have occurred in constant dollar per student expenditures at both elementary—secondary and university levels. In contrast to the early to late 1970's when provinces contributed ever larger proportions of the necessary funds, since that time both federal and municipal governments have been forced to increase their share of educational funding. These changes are examined not just in terms of intergovernmental relations but more importantly in terms of the fiscal crisis of the state.